Work engagement and its association with emotional intelligence and demographic characteristics among nurses in Palestinian neonatal intensive care units - Ibrahim Aqtam; Ahmad Ayed; Ahmad Batran; Moath Abu Ejheisheh; Riham H. Melhem; Mustafa Shouli (PLoS ONE, 2025)
Introduction Work engagement, defined as a positive, fulfilling, work-related state of mind characterized by vigor, dedication, and absorption, is crucial for nurse retention and quality of care in high-stress environments. Neonatal Intensive Care Units (NICUs) present unique emotional and psychological challenges for nurses, necessitating skills like emotional intelligence (EI) to enhance work engagement. This study investigates the association between EI, demographic factors, and work engagement among Palestinian NICU nurses. Methods A cross-sectional, descriptive correlational design was employed during February-April 2025. Of 230 nurses invited, 207 completed the survey (response rate = 90.2%) across 12 Palestinian NICUs using convenience sampling. Data analysis was conducted using descriptive statistics, Pearson’s correlation, and multiple linear regression via SPSS v26. Validated tools, the Schutte Self-Report Emotional Intelligence Test (SSEIT) and Utrecht Work Engagement Scale (UWES), were used. Results Emotional intelligence (EI) demonstrated a strong positive correlation with work engagement (r = 0.693, p < 0.001), accounting for 48.0% of the variance in engagement scores. Age (B = 0.463, β = 0.535, p = 0.002), female gender (B = −2.250, β = −0.115, p = 0.017), and rotating shifts (B = 1.579, β = 0.105, p = 0.028) were significant predictors. EI was the strongest predictor (B = 0.358, β = 0.593, p < 0.001). The EI subdimension “utilizing emotions” scored highest (M = 47.3 ± 5.8). Discussion The findings demonstrate strong associations between EI and engagement in high-stress NICU environments. Based on these findings, we propose implementing comprehensive EI training programs in nursing curricula, establishing mentorship programs to address age-related disparities, and developing gender-sensitive workplace policies to optimize work engagement and improve patient care quality.